2022
DOI: 10.1139/cjfas-2021-0178
|View full text |Cite
|
Sign up to set email alerts
|

Potential for codends with shortened lastridge ropes to replace mandated selection devices in demersal trawl fisheries

Abstract: In many trawl fisheries, codend size selectivity is supplemented by adding selection devices to the gear. In the Barents Sea gadoid fishery, combining diamond mesh codends with sorting grids is compulsory. However, the use of grids increases the costs and complexity of the gear, causing discontent among fishermen and prompting researchers to seek alternative solutions. Lastridge ropes are ropes attached to the selvedges of the codend. In this study, we tested the effect of shortening the lastridge ropes of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
0
12
1
Order By: Relevance
“…There are many simple options, however, that need to be tested and considered. For instance, using the square mesh panels in the diamond-mesh codends (Graham and Kynoch, 2001;Cuende et al, 2020;Kennelly and Broadhurst, 2021), shortening the lastridge ropes (Sistiaga et al, 2021), and adding artificial stimuli (Krag et al, 2017;Grimaldo et al, 2018;Melli et al, 2018;Ingoĺfsson et al, 2021) have been demonstrated to be simple and effective modifications to improve the size selectivity. It is suggested that future investigations should test and evaluate these modifications to further improve the size selectivity and catch efficiency of trawl fisheries for mantis shrimp in the SCS.…”
Section: Discussionmentioning
confidence: 99%
“…There are many simple options, however, that need to be tested and considered. For instance, using the square mesh panels in the diamond-mesh codends (Graham and Kynoch, 2001;Cuende et al, 2020;Kennelly and Broadhurst, 2021), shortening the lastridge ropes (Sistiaga et al, 2021), and adding artificial stimuli (Krag et al, 2017;Grimaldo et al, 2018;Melli et al, 2018;Ingoĺfsson et al, 2021) have been demonstrated to be simple and effective modifications to improve the size selectivity. It is suggested that future investigations should test and evaluate these modifications to further improve the size selectivity and catch efficiency of trawl fisheries for mantis shrimp in the SCS.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the selection process occurs in the codend, i.e., the end of the trawl where the catch accumulates (Wileman et al 1996). Diamond-mesh codends are the most widely applied designs and have traditionally been used in the majority of demersal trawl fisheries due to their simple structure and ease of operation (He, 2007;Wienbeck et al 2011;Sistiaga et al 2021). However, multiple studies have shown that diamond-mesh codends do not maintain a constant mesh openness while trawling, due to their flexibility (e.g., Robertson and Stewart, 1988;Reeves et al 1992;Herrmann, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the suboptimal size selection by the codend alone, some fisheries have supplemented this with additional selective devices to achieve a sharper selection curve such as the grid systems 'Flexigrid' commonly used in the Barents Sea demersal trawl fishery or square mesh panels like BACOMA used in Baltic Sea (Sistiaga et al 2010 andWienbeck et al 2014). However, a better approach could be to stabilize the selection process in the codend, thus avoiding the need for additional selection devices as they often require more handling and increase the cost (Sistiaga et al 2021).…”
mentioning
confidence: 99%
“…In general, all studies show that size selectivity for roundfish species was improved because significantly more under-sized individuals were released when shortened LR were used compared to equivalent non-shortened LR codends. Further, a recent study demonstrated that higher OAs are available in shortened LR codends compared to the standard ones and that size selection curves of different species can be explained by higher OAs (Sistiaga et al, 2021). Specifically, diamond meshes in non-shortened LR codends can include meshes with OAs in between 15 and 60º (Herrmann et al, 2009), whereas codends with 15% shortened LR can include mesh OAs between 40-90º and slack meshes (Sistiaga et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, this higher availability does not necessarily mean that fish utilize them to escape. Sistiaga et al (2021), for example, showed that mesh OAs contributing to the explanation of the size selection curves of different species could differ, meaning that although some specific OAs were available, these would not contribute to the size selectivity of all species. Shortened LR has greater influence in meshes further from the catch accumulation zone, which are often the ones less opened as the catch builds up.…”
Section: Introductionmentioning
confidence: 99%